Strategi Public Relations Garda Pangan dalam Mensukseskan Pelaksanaan Program Food Rescue - Shania, Louisa Vanessa; Edelweis Putri Prima (LPPM Stikosa-AWS, 2024)
Food waste has become a serious issue in Indonesia that requires urgent attention. The Food Rescue program offers significant benefits in reducing food waste and its negative environmental impact. The purpose of this research is to understand the Public Relations strategies employed by organizations to introduce and successfully implement the Food Rescue program to the public. Garda Pangan utilizes a Strategy of Publicity, which includes conducting campaigns, leveraging social media, and collaborating with mass media to disseminate information to the community. Garda Pangan practices seven types of Public Relations, including publicity, events, news, corporate identity, community involvement, lobbying and negotiation, and social responsibility. They also apply the Two-Way Symmetrical model, emphasizing open dialogue, transparency, and mutual understanding between the organization and its public.